MOTIF PENGGUNA TIKTOK DALAM MENDAPATKAN FOR YOUR PAGE (FYP) PADA KALANGAN REMAJA KOTA DENPASAR (E-Jurnal Medium, 2022)
TikTok is an application that provides a place for users to be creative in creating content in the form of videos. The way the TikTok for your page algorithm works is based on user interaction, video information, and account settings. The purpose of this study was to find out the motives of TikTok users in getting for your page (fyp) among teenagers in Denpasar City. The data in this quantitative descriptive study were collected using a questionnaire and analyzed using descriptive statistical analysis techniques. the results of the study show that the motive that most encourages teenagers in Denpasar to upload TikTok videos using the hashtag for your page (fyp) is the motive to fill spare time, while The motive that does not encourage teenagers in the city of Denpasar to upload TikTok videos using the hashtag for your page (fyp) is the economic motive. Keywords: Motive, TikTok Video, For Your Page, Teenager